#TITLE_ALTERNATIVE# - IKHSAN SYAHBANA (NIM : 15107067) ; (Pembimbing : Prof. Ketut Wikantika, Ph.D. ; Dr. Soni Darmawan, M.
The precision and accuracy of data in planning and development of an area is necessary in order to provide accurate results in reviewing the development of an area. One of the important information is land cover data changes. The purpose of this study is to indentify changes of land cover. The study was conducted in the coastal zone of Langkat North Sumatra which has potential in agribusiness area. The Study of land cover changes observed for 3 years using remote sensing data of Landsat Images in 2001, 2006, and 2011. This data are processed by Supervised Classification Method using OBIA techniques. In this technique, each images segmented into homogeneous regions using the right parameters for a multiple level data. For the quality of image classification results are expressed in matrix errors using data ground truth image with higher spatial resolution. The result of OBIA classification technique is about 70% overall accuracy. This research concluded that the changes from forest and plantation is quite significant. For forest, itÃ‚Â’s decreased about 63 % or 17452 Ha in 2006 and plantation area increased about 89 % or 14854 Ha .